Perceptions of Mathematics Education Professional Teacher Education Program (PPG) Students towards the PPG Program - Musa, Hastuty; Rusli, Rusli; Jufri, Hasrini (ARRUS Journal of Mathematics and Applied Science, 2024)
The Pre-Service Professional Teacher Education (PPG) program is designed to equip prospective teachers with the knowledge, skills, and professional values necessary to become qualified teachers. This research aims to investigate the perceptions of PPG students towards the Pre-Service PPG program, particularly in terms of curriculum, teaching methods, lecturers, and facilities. A descriptive research method was employed using a survey technique. Data was collected through questionnaires distributed to 102 Pre-Service PPG students via Google Forms. The research findings revealed that the majority of students (99.65%) perceived that the PPG program can enhance their professional competence. They rated the Pre-Service PPG program's curriculum as relevant to the needs of prospective teachers (99.1%), its teaching methods as varied and engaging (99.2%), its facilities as adequate (99%), its field practice support as exceptional (100%), its character and soft skills development as outstanding (100%), and its administrative and financial support as sufficient (89.7%). These findings indicate that the Pre-Service PPG program has been successful in equipping prospective teachers with the knowledge, skills, and professional values required to become qualified teachers. The positive perceptions of PPG students towards the Pre-Service PPG program serve as an indicator that this program has fulfilled its objectives in enhancing teacher quality in Indonesia.